2020
DOI: 10.1038/s41597-020-00599-8
|View full text |Cite
|
Sign up to set email alerts
|

A global map of terrestrial habitat types

Abstract: We provide a global, spatially explicit characterization of 47 terrestrial habitat types, as defined in the International Union for Conservation of Nature (IUCN) habitat classification scheme, which is widely used in ecological analyses, including for quantifying species' area of Habitat. We produced this novel habitat map for the year 2015 by creating a global decision tree that intersects the best currently available global data on land cover, climate and land use. We independently validated the map using oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
120
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(121 citation statements)
references
References 61 publications
0
120
0
1
Order By: Relevance
“…We assessed the intactness of coastal regions in proximity to tidal flats (Murray et al 2019), saltmarshes (Mcowen et al 2017), mangroves (Bunting et al 2018), seagrasses (UNEP-WCMC 2003), estuaries (Alder 2003), kelp forests (Mora-Soto et al 2020), coral reefs (UNEP-WCMC et al 2018), savannah (Jung et al 2020), deserts (Jung et al 2020), rocky areas (Jung et al 2020) and forests (Jung et al 2020). This was achieved by buffering the polygons representing each habitat type by 50 km (a radius equal to the radius used to quantify coastal intactness) and summarising the distribution of coastal intactness values within the buffer.…”
Section: Methodsmentioning
confidence: 99%
“…We assessed the intactness of coastal regions in proximity to tidal flats (Murray et al 2019), saltmarshes (Mcowen et al 2017), mangroves (Bunting et al 2018), seagrasses (UNEP-WCMC 2003), estuaries (Alder 2003), kelp forests (Mora-Soto et al 2020), coral reefs (UNEP-WCMC et al 2018), savannah (Jung et al 2020), deserts (Jung et al 2020), rocky areas (Jung et al 2020) and forests (Jung et al 2020). This was achieved by buffering the polygons representing each habitat type by 50 km (a radius equal to the radius used to quantify coastal intactness) and summarising the distribution of coastal intactness values within the buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Major occurrences of croplands were taken from the map of Habitat type 14.1 by Jung et al (2020) based on the IUCN Habitats Classification Scheme (version 3.1) (IUCN, 2012). We compared this to cropping areas in consensus land-cover maps (Tuanmu & Jetz, 2014) and found that maps of Jung et al (2020) more closely matched the concept of T7.1. Occurrences were extracted from fractional aggregated 1 km resolution base data (Jung et al 2020), approximating 30 arc seconds spatial resolution.…”
Section: T71mentioning
confidence: 99%
“…We compared this to cropping areas in consensus land-cover maps (Tuanmu & Jetz, 2014) and found that maps of Jung et al (2020) more closely matched the concept of T7.3. Occurrences were extracted from fractional aggregated 1-km resolution base data (Jung et al, 2020), approximating 30 arc seconds spatial resolution.…”
Section: T73mentioning
confidence: 99%
See 1 more Smart Citation
“…IUCN standardized habitat definitions independently of taxonomy or geography. However, IUCN habitat classes are not spatially explicit, although recent efforts have attempted to delimit them (Jung et al, 2020). Land-cover classes derived from remote sensing have been widely used as a surrogate of habitat (e.g.…”
Section: Introductionmentioning
confidence: 99%